Utilisation of genes and SNPs in selective breeding of small ruminants for anoestrus period reduction - Antonopoulou, D; Giantsis, I; Avdi, M (Journal of the Hellenic Veterinary Medical Society, 2025)
Small ruminants are characterised by large anoestrus periods in temperate latitudes due to photoperiodism. This is a major obstacle in sheep and goat farming in several countries where milk from these animals constitute important products for national economies. In an effort to reduce the usage of exogenous hormones administration for oestrus induction and there reproduction and milk production throughout the year, genetic improvement scoping to non seasonal dependent breeding could be a promising alternative. Keeping this in mind, this mini review presents the most commonly studied genes that have been associated with reproduction seasonality in small ruminants, as well as and most importantly the successful selective breeding schemes that have achieved reproduction seasonality elimination. Although numerous genes and Single Nucleotide Polymorphisms (SNPs) have been associated with seasonality as listed here, they have been scarcely utilised in selective breeding programs, calling their efficiency as selective breeding targets into question. Future research should, hence, evaluate chronic data from implementation of selective breeding schemes in order to facilitate their validity in various breeds.